Fragments and Ellipsis - Merchant, Jason (Linguistics and philosophy, 2004)
Fragmentary utterances such as 'short' answers and subsentential XPs without linguistic antecedents are proposed to have fully sentential syntactic structures, subject to ellipsis. Ellipsis in these cases is preceded by A′-movement of the fragment to a clause-peripheral position; the combination of movement and ellipsis accounts for a wide range of connectivity and anti-connectivity effects in these structures. Fragment answers furthermore shed light on the nature of islands, and contrast with sluicing in triggering island effects; this is shown to follow from an articulated syntax and the PF theory of islands. Fragments without linguistic antecedents are argued to be compatible with an ellipsis analysis, and do not support direct interpretation approaches to these phenomena.